ANALISA KINERJA OPERASIONAL KRL COMMUTER LINE JURUSAN YOGYAKARTA-SOLO - Arifin, Tendhi Nur; Sodikin, Sodikin; Tantin, Tantin (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
This study aims to analyze the operational performance of the KRL Commuter Line heading for Yogyakarta-Solo, with a focus on transportation capacity, departure frequency, and schedule management. The approach used in this study is quantitative descriptive, where data is collected through direct observation, and collection of supporting documents In addition, operational data from PT KAI is also analyzed to obtain a comprehensive picture of the operational performance of the KRL. The main variables studied include transportation capacity, Load Factor, departure frequency, and schedule management. The results of the study show that during peak hours, the Load Factor of KRL often exceeds 100%, which indicates a high passenger density. The carrying capacity of KRL needs to be increased, both by increasing the number of cars and increasing the frequency of departures, to reduce congestion and increase comfort. Additionally, better schedule management and real-time monitoring of passenger density can help optimize operations. This study provides recommendations for PT KAI in terms of improving the capacity of the carriages, increasing the frequency of departures, and improving comfort facilities on the train to increase passenger satisfaction. The results of this study are expected to be a reference in efforts to improve the quality of KRL Commuter Line services, especially on the Yogyakarta-Solo route.